2006
DOI: 10.1210/jc.2006-1391
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Study of Effects of Dietary Magnesium Oxide Supplementation on Bone Mineral Content in Healthy Girls

Abstract: Oral Mg oxide capsules are safe and well tolerated. A positive effect of Mg supplementation on integrated hip BMC was evident in this small cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(37 citation statements)
references
References 27 publications
0
34
0
3
Order By: Relevance
“…Aydin and colleagues (2010) reported the effects of Mg supplementation on bone turnover suppression in postmenopausal women [4]. Also, the positive effects of Mg supplementation on hip BMC in peri-adolescent girls has been previously documented [5]. Meanwhile, higher Mg intake from foods or supplements may parallel higher intake of nutrients thought to be beneficial to bone health [14,24,25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aydin and colleagues (2010) reported the effects of Mg supplementation on bone turnover suppression in postmenopausal women [4]. Also, the positive effects of Mg supplementation on hip BMC in peri-adolescent girls has been previously documented [5]. Meanwhile, higher Mg intake from foods or supplements may parallel higher intake of nutrients thought to be beneficial to bone health [14,24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has also shown the effects of Mg supplementation on bone turnover suppression in postmenopausal women [4]. It was reported that a positive effect of Mg supplementation on hip bone mineral content (BMC) was evident in periadolescent girls [5]. However, previous studies regarding Mg supplementation and bone health are mostly about postmenopausal women or OVX animal models, both of which have high risk for osteoporosis.…”
Section: Introductionmentioning
confidence: 99%
“…Захисна дія підвищеного надходження Mg на якість КТ була задокументована у здорових жінок за допомогою методу ультразвукового вимірювання щільності п'яткової кістки [26]. Позитивний ефект додавання Mg на накопичення кісткової маси стегнової кістки показаний групою авторів на практично здорових дівчатах [27].…”
Section: зміни стану кісткової тканини за умов надмірного вмісту Mgunclassified
“…Also in humans magnesium deficiency contributes to osteoporosis; in Framingham study magnesium intake was positively associated with bone mass density (25). Recently, the protective effect of high magnesium intake on bone quality was documented in healthy women using ultrasound measurement in calcaneus (26) and a trial shows a positive effect of magnesium supplementation on the accrual of bone mass in the hip of young women (27). Several direct and indirect mechanisms contribute to the effects of low magnesium on bone density: low magnesium can directly affect the bone by altering the structure of apatite crystals; magnesium deficiency is also associated with reduction of PTH and 1,25(OH 2 ) D levels and low grade inflammation and endothelial dysfunction, with a well-known relation between inflammation and bone loss (28).…”
Section: Magnesiummentioning
confidence: 99%